A rare cause of constipation - Monteiro, Sara; Teixeira, Beatriz; Couto, Cristiana; Silva, Gisela (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
In Pediatrics, functional etiology accounts for the vast majority of constipation cases, while neoplastic etiology is rare. The authors describe the case of a 14-year-old male with a history of constipation that progressively worsened and became refractory to medical treatment. On physical examination, the patient had a distended and painful abdomen with a palpable mass in the hypogastric region. An abdominopelvic computed tomography scan revealed multiple masses highly suggestive of a neoplastic process. Anatomopathologic examination confirmed the diagnosis of desmoplastic small round cell tumor (DSRCT). DSRCT is an extremely rare and aggressive malignancy that can present without constitutional symptoms. This case highlights the importance of recognizing warning signs in patients presenting with constipation.